2008
DOI: 10.1002/eqe.816
|View full text |Cite
|
Sign up to set email alerts
|

Parameter identification of torsionally coupled shear buildings from earthquake response records

Abstract: SUMMARYThis paper presents an efficient procedure to determine the natural frequencies, modal damping ratios and mode shapes for torsionally coupled shear buildings using earthquake response records. It is shown that the responses recorded at the top and first floor levels are sufficient to identify the dominant modal properties of a multistoried torsionally coupled shear building with uniform mass and constant eccentricity even when the input excitation is not known. The procedure applies eigenrealization alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…To identify complete mode shapes one needs to have simultaneous vibration records at all floor levels or use mode shape interpolation techniques. It has been shown that vibration records collected at top and first floor level are sufficient to get the complete mode shapes of a symmetric torsionally-coupled shear building [18,19]. The mode shape interpolation techniques can be applied if the building is symmetric and follows uniform shear criterion [9].…”
Section: Modal Parameter Identification Techniquementioning
confidence: 99%
“…To identify complete mode shapes one needs to have simultaneous vibration records at all floor levels or use mode shape interpolation techniques. It has been shown that vibration records collected at top and first floor level are sufficient to get the complete mode shapes of a symmetric torsionally-coupled shear building [18,19]. The mode shape interpolation techniques can be applied if the building is symmetric and follows uniform shear criterion [9].…”
Section: Modal Parameter Identification Techniquementioning
confidence: 99%
“…The initial natural frequencies can be obtained by the vibration at the top oor [47]. [26] shows that the top and the ground levels are well enough to get the mode shapes of a symmetric torsionally-coupled shear building.…”
Section: Bidirectional Modeling Of Controlled Building Structuresmentioning
confidence: 99%
“…An identification of dynamic models of a building structure using multiple earthquake records has been developed by Hong, Betti, and Lin (2009). Parameter identification of torsionally coupled shear buildings from earthquake response records has also been proposed by Hegde and Sinha (2008). Model updating of multistorey shear buildings for simultaneous identification of mass, stiffness and damping matrices using two different softcomputing methods has been developed by Khanmirza, Khaji, and Majd (2011).…”
Section: Introductionmentioning
confidence: 99%